Process optimization, characterization and economic evaluation of nanoparticles derived from galvanic sludge for photodegradation of 4-nitrophenol under natural sunlight. (15th October 2022) - Muthukumar, Chandhini; Changmai, Murchana; Vincent, S.; Raju, Kumar; Mathai, Jessin; Damale, Shailesh; B G, Prakash Kumar
Abstract: The United Arab Emirates has an average of 10 h of sunlight and is available almost throughout the year. This energy has a huge potential to be utilized in photodegrading wastewater. To engineer a sustainable photocatalyst, the waste (galvanic sludge) obtained from the galvanization industry was utilized to degrade 4-nitrophenol under natural sunlight. Detailed morphological, chemical, and optical characterization of galvanic sludge (GS) was performed by UV-DRS, FESEM-EDX, XRD, XPS, PL, FTIR, and GC-MS. RSM-CCD was utilized for optimizing the three key parameters, such as pH, photocatalyst loading, and 4-nitrophenol concentration. The highest photodegradation efficiency of about 94.5% was obtained for a 4-nitrophenol concentration of 30 ppm with a photocatalyst loading of 0.02 g at a pH of 6 with 0.01 mL of H2 O2 . Based on the analysis of variance results, the R 2 value of the overall model was 98.1%, which indicated that the obtained model was well suited for degrading 4-nitrophenol. An economic evaluation was performed for applicability in the real world. For this photodegradation model, the cost of treatment was determined to be USD 17.5/m 3 . To the best of our knowledge, for the first time we have innovatively used GS as an efficient photocatalyst for treating 4-nitrophenol. Graphical abstract: Image 1 Highlights: The galvanic sludge obtained from the galvanization industry was reported as a photocatalyst. Process parameters were optimized by response surface methodology using the central composite design. Galvanic sludge imparted excellent efficiency (94.5%) in photodegrading 4-nitrophenol under natural sunlight. The total treatment cost for photodegradation of 4-nitrophenol was determined to be USD 17.5/m 3 .